Studi Keamanan Pangan Makanan Jajanan Anak Sekolah Dasar Pada Beberapa Sekolah Dasar Di Negeri Amahusu Kota Ambon - Reilely, Prisilya H; Mailoa, Meitycorfrida; Nendissa, Sandriana J (Jurnal Agrosilvopasture-Tech, 2025)
School-age children are the nation’s investment because they are the next generation. School age is a period of growth and development of children towards adolescence, so it is necessary to provide nutrition of good quality and quantity. Adequate intake of permitted foods that are safe for consumption is very important. The habit of consuming street food is very popular among school children. It is important to pay attention to the food environment in schools, because there are quite a lot of unhealthy foods available in schools. This study aims to determine and study food safety from a microbiological perspective in several elementary schools in Amahusu State, Ambon City. This research is descriptive. The research was conducted in two stages, including a survey (questionnaire distribution) and a microbiological test (ALT). The result of the study shows that samples A1 (Fried Rice) and A2 (Bakpao Cake) at SD Negeri 1 Amahusu have a number of microbes that are still below the threshold set by SNI, as well as samples B1 (Fried Rice) and B2 (Donut Cake), the number of microbes is still below the threshold set by SNI. Where as in samples C1 (Fried Rice) and C2 (Egg Meatballs) the number of mirobes passed through the limits set by SNI. Apart from that, the implementation of sanitation and hygiene has not been carried out optimally by sellers at elementary schools in Amahusu, Ambon City.